1995
DOI: 10.1088/0022-3727/28/4/027
|View full text |Cite
|
Sign up to set email alerts
|

Design, construction and testing of explosive-driven helical generators

Abstract: This paper describes the development of a very efficient computer model for the design and performance prediction of explosive-driven helical generators. The model is based on simple theoretical considerations. Validation of the model is achieved by comparing the theoretical and measured performances of existing both high- and low-energy generators. It is shown that, although the basic model predicts accurately the load current history of high-energy generators, a somewhat more elaborate model is needed for lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…12 The time varying resistance R g (t) in this model only represents the dc resistance, which is calculated by the image-current model demonstrated in Ref. 13. The flux conservation coefficients can be determined by comparing the calculation results with the experimental data of similar generators or prototype of the generator to predict.…”
Section: Resistance Calculationmentioning
confidence: 99%
“…12 The time varying resistance R g (t) in this model only represents the dc resistance, which is calculated by the image-current model demonstrated in Ref. 13. The flux conservation coefficients can be determined by comparing the calculation results with the experimental data of similar generators or prototype of the generator to predict.…”
Section: Resistance Calculationmentioning
confidence: 99%
“…Although the calculation methods in [7] were designed for DS-FCGs, the authors here found them to be adaptable for use in the calculation of FT-FCG inductances. Calculations for the resistance curves are carried out with an image-current model based on techniques found in [8].…”
Section: Calculation Of Inductance and Resistance Curvesmentioning
confidence: 99%
“…The time-varying resistance curves were calculated using image-current models found in [8] and [10]. Typically, complex profiles for FCG resistances are desired because they account for a large portion of flux loss seen in FCG experiments.…”
Section: B Time-varying Resistancementioning
confidence: 99%
“…More recently developed generators have been described at the megagauss conferences, with energies up to 90 MJ and fuse-type opening switches to increase the output voltage and to shorten the rise time. An overview over design problems and performance calculations is contained in the recent paper by Novac et al [128]; this describes a helical generator built with fairly simple resources at a university laboratory.…”
Section: Flux Compression Systems With An External Loadmentioning
confidence: 99%